Outcomes of laparoscopic transabdominal preperitoneal hernia repair in the elderly population: a retrospective cohort study - Dawid Golik; Krzysztof Jędras; Przemysław Sroczyński; Grzegorz Dobkowski; Michał R. Janik (Videosurgery and Other Miniinvasive Techniques)
Introduction: Hernia repair is a common procedure, especially among the elderly. In the face of rising life expectancy, adequate hernia management in older adults is crucial. Laparoscopic transabdominal preperitoneal patch plasty (TAPP) for hernia repair is minimally invasive, but poses challenges in the elderly due to a larger number of comorbidities.